2018
DOI: 10.1016/j.jcte.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Circulating PANDER concentration is associated with increased HbA1c and fasting blood glucose in Type 2 diabetic subjects

Abstract: HighlightsPANcreatic-DERived factor (PANDER) is a novel hormone regulating glucose levels.Fasting PANDER levels were measured in T2D and non-T2D matched subjects from U.S.Associations between PANDER and other hormones or metabolic parameters were examined.PANDER was associated with increased HbA1c and fasting blood glucose in T2D subjects.PANDER was not associated with adiponectin, HOMA-β and HOMA-IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(34 reference statements)
0
6
0
1
Order By: Relevance
“…Another clinical report confirmed that serum PANDER level is increased in patients with metabolic syndrome, and an increase in circulating PANDER level can predict metabolic syndrome in Chinese population . An increase in serum PANDER levels have been reported to be associated with pancreatic β cell dysfunction and hyperglycemia in other races . Overall, these important clinical studies revealed that circulating PANDER is a unique diagnostic biomarker for diabetes and metabolic syndrome, and it is necessary to further study the mechanism(s) of PANDER in the regulation of glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Another clinical report confirmed that serum PANDER level is increased in patients with metabolic syndrome, and an increase in circulating PANDER level can predict metabolic syndrome in Chinese population . An increase in serum PANDER levels have been reported to be associated with pancreatic β cell dysfunction and hyperglycemia in other races . Overall, these important clinical studies revealed that circulating PANDER is a unique diagnostic biomarker for diabetes and metabolic syndrome, and it is necessary to further study the mechanism(s) of PANDER in the regulation of glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 81%
“…29 An increase in serum PANDER levels have been reported to be associated with pancreatic β cell dysfunction and hyperglycemia in other races. 18,19 Overall, these important clinical studies revealed that circulating PANDER is a unique diagnostic biomarker for diabetes and metabolic syndrome, and it is necessary to further study the mechanism(s) of PANDER in the regulation of glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, FAM3B has been suggested to be a causal gene for type 2 diabetes. In humans and mice, increased circulating FAM3B/PANDER levels are associated with hyperglycemia, pancreatic β-cell dysfunction, and insulin resistance (54)(55)(56)(57)(58). Second, FAM3B has been reported to act as an oncogene that, when expressed, promotes the progression of several types of cancer, including colon cancer, prostate cancer, esophageal cancer, and gastric cancer (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%